The global financial crisis, neoclassical economics, and the neoliberal years of capitalism - Luiz Carlos Bresser-Pereira (Revue de la Régulation)
The 2008 global financial crisis was the consequence of financialization or the creation of massive fictitious financial wealth, and of the hegemony of a reactionary ideology, namely, neoliberalism, based on the self-regulated and efficient markets.Although laissez faire capitalism is intrinsically unstable, the lessons from the stock-market crash of 1929 and the Great Depression of the 1930s were transformed into theories and institutions that led to the “30 glorious years of capitalism”. Yet, after the late-1970s, a coalition of rentiers and “financists” achieved hegemony, deliberately promoted deregulation and created financial innovations that made these markets even more risky. These were the “neoliberal years of capitalism”. Neoclassical economics played the role of a meta-ideology as it legitimized, mathematically and “scientifically”, neoliberal ideology and deregulation. From this crisis a new democratic capitalist system will emerge, though its character is difficult to predict. It will not be so financialized, and probably the tendencies present in the 30 glorious years toward global and knowledge-based capitalism, as well as the tendency to improve democracy by making it more social and participatory, will be resumed.